Plant growth-promoting rhizobacteria and ash applications enhance tomato yield in Ultisol - Mahmudi Mahmudi; Ongki Aleksa Samson; Sherly Oktarianti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2026)
Plant growth-promoting rhizobacteria (PGPR) and cattle manure ash applied to Ultisol can enhance soil fertility and tomato productivity. The study aimed to analyze the effects of PGPR and cattle manure ash on the growth and yield of tomato in Ultisol. The experiment was conducted in Kubu Raya Regency, West Kalimantan, Indonesia, from March to July 2025, using a factorial completely randomized design with PGPR application (with and without PGPR) and cattle manure ash (dolomite as control, 5, 10, 15, and 20 ton ha-1). A total of 10 treatment combinations were evaluated, with 3 replications. The PGPR significantly improved physiological performance, growth, and yield of tomato in Ultisol. Nitrogen and phosphorus uptake increased by 0.65 g per plant and 0.23 g per plant, respectively, along with higher relative growth rates. The combination of PGPR and 5 ton ha-1 cattle manure ash enhanced plant height and shoot dry weight to levels similar to dolomite, while optimal root dry weight occurred at 10 ton ha-1 ash. Fruit number increased at 15 ton ha-1 ash, comparable to dolomite, although fruit weight per plant remained slightly lower. The results indicate that cattle manure ash can partially replace dolomite in tomato cultivation, can increase vegetative growth at 5 ton ha-1 and certain yield components at higher rates of 10 ton ha-1. Keywords: microorganisms; nutrient uptake; plant physiology; soil fertility; tomato productivity